Speciation of some trace elements in water samples after preconcentration on activated carbon by neutron activation analysis - Mohd Yusof, Alias; Rahman, Md. Mokhlesur; Wood, Abdul Khalik (SpringerLink, 2004)
A new filtering column has been developed on the covalent attachment of chelating functionalities to simple, highly hydrophilic adsorbent material,which can then complex heavy metal ions irreversibly and targeted towards toxic metals removal. The capacity of the chemically modified sorbent (modified charcoal) materials used in this work was evaluated for the above mentioned heavy metal ions in the presence of iron ions and simulated water samples. The methods are based on preconcentrations of the elements of interest on activated carbon and zirconium loaded activated carbon using specific conditions of pH and oxidation states followed by a final determination by neutron activation analysis (NAA). It has been investigated that zirconium loaded activated carbon is able to adsorb As (V), Se (VI), Cr (VI) and Hg (II) at any pH while activated carbon is able to adsorb As (III), Se (IV), Cr (III) and Hg(I) at higher pH.